(untitled) (Al-Academy, 2024)
The aim of the current research is to identify the effect of the thinking maps strategy in developing productive thinking among female students of the Institute of Fine Arts in the subject of analysis and art criticism. To measure the size of the effect, the researcher adopted the experimental method with two experimental and control groups with a pre- and post-test, and the research tool was a measure of productive thinking for a sample of female students in the Fine Arts Department. The number of students was (17). The data was analyzed using the SPSS statistical package, and the results were shown There is a statistically significant difference between the average scores of female students in the two research groups on the post-productive thinking scale, in favor of the experimental group. There is a statistically significant difference between the average ranks of the scores of the two research groups in the pre- and post-productive thinking scale, and the alternative hypothesis is accepted, which states that there are differences between the average scores of the two research groups in the pre- and post-productive thinking scale